ROLE OF PROBIOTICS ADMINISTRATION ON LABORATORY MICE AND THEIR EFFECTS ON THE BLOOD PHYSIOLOGICAL AND IMMUNOLOGICAL PARAMETERS - Fatin Askander; Haider Alrafas; Hanaa Ibraheim (Basrah Journal of Veterinary Research)
The microbiome plays critical roles in the training and development of major components of the host's innate and adaptive immune system, while the immune system orchestrates the maintenance of key features of the host Other probiotic administration has a larger impact on body immunity and increases anti-inflammatory cells and polarize the immune response towards the body immunity.In this study, we examine how regular administration of probiotics Lacticaseibacillus rhamnosus and Bacillus clause) to Lab mice will impact the innate immune response, including the total number of lymphoid cells on physiological parameters, and blood biochemical levels, and how these factors affect the potential outcome of experiments. Sixty female mice were used in this study seven days with a probiotics combination including Lacticaseibacillus rhamnosus and Bacillus clause ( 100 ul oral gavage ) blood samples were collected to evaluate hematological and biochemical parameters the data revealed that there were no significant differences in the Hb and RBC values, however, the WBC count in peripheral blood and local lymph nodes of animals increased significantly after 7 days of treatment. Also, there is a significant change in ILC3 probiotic administration In the case of biochemical parameters of blood including ALT, AST, creatinine, and urea. These results revealed that there were no significant changes in these parameters in all experimental periods. the regular treatment of probiotics is one of the most important elements that may affect the general immune conditions of lab mice especially the WBCs and the innate immune responses.